2005
DOI: 10.1021/jf048197s
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Ascorbic Acid and Oxalate Levels in the Fruit of Actinidia chinensis Tissues and Genotypes

Abstract: Ascorbic acid and total oxalate were measured in fruit from six genotypes of Actinidia chinensis. Ascorbic acid was separated from oxalate in fruit extracts by HPLC and quantified from absorbance at 245 nm, whereas oxalate was measured enzymatically in the HPLC eluate. Levels of whole fruit mean ascorbic acid in the different genotypes ranged from 98 to 163 mg/100 g of fresh weight (FW), whereas mean oxalate varied between 18 and 45 mg/100 g of FW. Ascorbic acid was highest in the inner and outer pericarp, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 40 publications
2
54
0
1
Order By: Relevance
“…Kiwi (Actinida chinesis) was reported to contain a range of 18-45 mg total oxalate/100 g fresh weight in different genotypes (Rassam & Laing, 2005). The present study yielded 37.4 mg total oxalate and 6.6 mg soluble oxalate per 100 g in kiwifruits when using the hot extraction method, while the cold extraction method yielded 30.6 mg total oxalate and 6.5 mg soluble oxalate per 100 g.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…Kiwi (Actinida chinesis) was reported to contain a range of 18-45 mg total oxalate/100 g fresh weight in different genotypes (Rassam & Laing, 2005). The present study yielded 37.4 mg total oxalate and 6.6 mg soluble oxalate per 100 g in kiwifruits when using the hot extraction method, while the cold extraction method yielded 30.6 mg total oxalate and 6.5 mg soluble oxalate per 100 g.…”
Section: Discussionmentioning
confidence: 43%
“…Previous work suggested that most fruits contain only small quantities of oxalate (Zarembski & Hodgkinson, 1962b), while some such as kiwifruit and star fruit (Carambola) were reported to be moderately high (Wang et al, 2006;Rassam & Laing, 2005). Kiwi (Actinida chinesis) was reported to contain a range of 18-45 mg total oxalate/100 g fresh weight in different genotypes (Rassam & Laing, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The retention time of oxalate ions in these conditions was t R = 13.73 ± 0.01 min. Previous reports (Rassam et al, 2005) and the experimental data suggested interference from sulfate ions on oxalate ion determination. A chromatogram of a standard mixture of equivalent amounts of sulfate and oxalate ions is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 75%
“…After water, tea is the second most popular beverage, but it contains high levels of oxalic acid (Sang et al, 2011). In the human body, oxalic acid is formed by the metabolism of glycine and ascorbic acid (Rassam et al, 2005). The role of oxalic acid in the human body is very significant, because its compounds are responsible for the stability of biological membranes (Melnik, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…There are few traditional approaches that offer hope and few established methods that are yet to gain popularity. Peeling of foods where plant pericarp has high calcium oxalate [83] seems to be an effective and economical way of reducing calcium oxalate. In addition, there are emerging pieces of evidence that raise the hope that several plants with huge drug and food potential can be better utilized by reduction or removal of calcium oxalate.…”
Section: Removal Of Calcium Oxalatementioning
confidence: 99%